Epidermal morphology of Nigerian species of synsepalum (sapotaceae) (1999)
The leaf epidermal morphology of three Nigerian species of Synsepalum has been studied by light microscopy. Epidermal cells are Irregular or polygonal with straight, curved, undulate or sinuate anticlinal walls. All taxa are amphistomntic although adaxial stomata are restricted to the veins and their vicinities. Stomatal type varies in the genus. Anomocytic stomata are present on both leaf surface of S. dulcificum and S. stipulation while cyclocytic and paracytic types are recorded in S. glycydorum on the adaxial and abaxial surfaces respectively. The periclinal divisions in the abaxial guard cells of S. stipulatum is diagnostic of the species. All taxa are glabrous but numerous trichome bases are found on the abaxial surface of S. glycydorum suggesting an early loss of hairs in leaf development A dichotomous key for identifying the species is presented.